(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article deals with the analysis of the problem of accidents in road transport in order to determine the statistics of vehicles that take into account the technical condition of vehicles and the road environment. Determined the impact on the efficiency of the braking process of vehicles in the production of autotechnical expertise of the safe technical condition of the car and the road environment.